90 A unique comparison between primary and secondary pulmonary hypertension: 15-year naturalistic follow-up study from the United Kingdom ACALM 'big data' registry. (May 2019) - Potluri, Rahul; Das, Debraj; Carter, Paul; Patel, Billal; Chalil, Shajil; Tymchak, Wayne; Kim, Daniel; More, Ranjit; Bainey, Kevin
Abstract : Background: Both primary and secondary pulmonary hypertension (PH) are independently associated with morbidity and mortality. Compared to primary PH, the underlying pathology in secondary PH remains diverse as seen in the WHO classification. As such, variation in long-term outcomes remains unclear. We examined the differences in clinical characteristics and long-term mortality between primary and secondary PH using the United Kingdom (UK) Algorithm for Co-morbidity, Associations, Length of stay and Mortality (ACALM) Registry. Methods: Out of 1, 816, 230 patients admitted to several hospitals in Northern England from January 2000 to July 2014 (15-year follow-up), 2895 patients with PH were identified using the UK ACALM study protocol. ACALM utilizes a 'big data' approach to amalgamate multiple datasets and ICD-10/OPCS-4 coding to identify patients with different diagnoses. In this study, primary PH was identified with an ICD-10 code of I270 (specific) and secondary PH included all other codes relating to PH. Results: Of our PH cohort, 1688 patients had primary PH (58.3%) and 1207 patients had secondary PH (41.7%). Table 1 shows the differences in selected clinical characteristics between both groups as well as crude mortality rates, readmissions and length of hospital stay. Kaplan-Meier curves for long-term survival are shown in figure 1. Cox-regression was performed for survival and found lower adjusted mortality with secondary PH compared to primary PH (adjusted HR 0.87, 95% CI [0.78–0.98], p=0.018). Conclusion: Date from the UK-ACALM 'big data' registry confirms poor long-term prognosis with both primary and secondary PH over a 15-year follow-up. Surprisingly, one in three patients will have died by 5-years. Improved survival was observed in secondary PH compared to primary PH possibly reflecting the treatment of reversible causes of secondary PH. Further studies are required to understand survival differences in this complex population, where therapies continue to evolve. Conflict of Interest: Nil